Creating International Responsibility: The Non-Prosecution of Sexual Violence Post Conflict as a Violation of Women’s Rights - Megan Nobert (Tilburg Law Review, 2012)
After a historical reconstruction of the crime of sexual assault in conflict and of its evolution in international criminal law, done by exploring the definition of sexual violence and the conditions and rules for prosecuting the crime, this article adds another vantage point to the thorny issue of tying the effects of sexual assault to human rights. By arguing that the non-prosecution of sexual violence results in a violation of women’s rights, the author proposes another level of protection under international law invoking the 'Convention on the Elimination of All Forms of Discrimination against Women (hereinafter: CEDAW)'. First, as the author has narrowed the focus of her article to female victims, the sexual assault can be considered a gender based crime of which non-prosecution may be discriminatory; the author examines whether this hypothesis is a violation of women’s freedom from discrimination under Article 1 of CEDAW. Second, as sexual assault in conflicts often leaves women with very serious health problems, this paper examines whether these effects of the crime are a violation of women’s right to health under Article 12 of CEDAW. This author will now use CEDAW to prove another level of violation on the part of the international community. If one can prove that non-prosecution of sexual violence is a violation of CEDAW - under international human rights law - States will have a further obligation to cease this internationally wrongful act.